Triple-Bundle Medial Collateral Ligament Reconstruction: The Medial Arrow Technique - Hesham Mohamed Gawish, M.D.; Mohamed Abdelmonsef Ibrahim Elghaish, M.Ch Ortho; Waleed Hamed Hamed Ebrahim Aziz, M.Ch Ortho; Emam Mohamed Ahmed Emam Ahmed, M.Ch Ortho; Ahmed Hassan Saad Abou Helwo, M.Ch Ortho; Ahmed Hassan Taha Waly, M.D. (Arthroscopy Techniques)
Medial knee injuries are common and sometimes overlooked in cases of anterior cruciate ligament injuries. Persistent anteromedial rotatory instability can lead to chronic pain and later anterior cruciate ligament reconstruction failure. Moreover, in cases with multiligamentous knee injuries, there may be combined anteromedial and posteromedial rotatory instabilities. In this Technical Note, a triple-bundle reconstruction of the superficial medial collateral ligament, the deep medial collateral ligament, and the posterior oblique ligament is described to address these instabilities.